2004
DOI: 10.1091/mbc.e04-03-0265
|View full text |Cite
|
Sign up to set email alerts
|

Localization of RNAs to the Mitochondrial Cloud inXenopusOocytes through Entrapment and Association with Endoplasmic Reticulum

Abstract: The germ cell lineage in Xenopus is specified by the inheritance of germ plasm, which originates within a distinct "mitochondrial cloud" (MC) in previtellogenic oocytes. Germ plasm contains localized RNAs implicated in germ cell development, including Xcat2 and Xdazl. To understand the mechanism of the early pathway through which RNAs localize to the MC, we applied live confocal imaging and photobleaching analysis to oocytes microinjected with fluorescent Xcat2 and Xdazl RNA constructs. These RNAs dispersed ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
183
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(194 citation statements)
references
References 73 publications
9
183
0
2
Order By: Relevance
“…As described previously (Chang et al 2004;Kosaka et al 2007;Li et al 2011;Peng et al 2009;Xu et al 2009), dazl colocalized with a cytoplasm structure, named the Balbiani body (BB) or mitochondrial cloud (MC) (King et al 2005), containing mitochondria, endoplasmic reticulum and germ plasm RNAs. In particular, this structure could be detected by a mitochondrial marker, such as MitoTracker.…”
Section: Gene Identificationmentioning
confidence: 61%
See 1 more Smart Citation
“…As described previously (Chang et al 2004;Kosaka et al 2007;Li et al 2011;Peng et al 2009;Xu et al 2009), dazl colocalized with a cytoplasm structure, named the Balbiani body (BB) or mitochondrial cloud (MC) (King et al 2005), containing mitochondria, endoplasmic reticulum and germ plasm RNAs. In particular, this structure could be detected by a mitochondrial marker, such as MitoTracker.…”
Section: Gene Identificationmentioning
confidence: 61%
“…og oogonia, sg spermatogonia, psp primary spermatocytes, ssp secondary spermatocytes, spd, spermatid. Bars (a, d) 50 μm, (b, e) 20 μm shown that dazl RNA of Xenopus (Chang et al 2004), zebrafish (Kosaka et al 2007), gible carp (Peng et al 2009), medaka (Xu et al 2009) and trout (Li et al 2011) are concentrated within the BB/MC, a spherical-shaped structure. Nonetheless, in Acipenser gueldenstaedtii (Zelazowska et al 2007), oocytes contain two different zones of cytoplasm, the homogeneous ooplasm and granular ooplasm, with the granular ooplasm corresponding to the BB/MC.…”
Section: Discussionmentioning
confidence: 99%
“…In the METRO pathway, mRNAs accumulate within a region of the Balbiani body, also called the mitochondrial cloud, in stage I oocytes (Chang et al, 2004), and then translocate to the vegetal cortex through a directional expansion of the mitochondrial cloud itself (Wilk et al, 2004). Interestingly, many mRNAs localized through the METRO pathway are also components of the germ plasm and involved in germ cell differentiation (Kloc et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Second, mRNAs passively diffusing through the cytoplasm can be bound and retained by anchoring proteins that are themselves localized to specific cellular sites. This system has been shown to function in at least two different systems: Xenopus oocytes 65 with the RNAs Xcat2 and Xdazl and Drosophila embryos with nanos mRNA. 66 Finally, RNAs can also be actively directed to a particular location.…”
Section: Protein Factors Involved In Rna Localizationmentioning
confidence: 99%